An Interactive Computerised Protocol for the Management of Hypertension - Evans, A. R.; Wilkes, E. R.; Absolon, P. J.; Denner, T. J.; Kaye, G. (Methods of Information in Medicine, 1985)
The management of hypertension using a computer within a hospital environment is well documented [4, 5, 6, 11, 15]. This paper describes the background, structure and use of an interactive care system designed to be used by general medical practitioners in their consulting rooms.A management plan (protocol) for the care of an “ideal hypertensive” patient was defined by a group of general practitioners. The method by which this plan was adapted and converted for use on the computer is described. The computer handles patient information according to the protocol, prompting and interacting with the physician in attempting to improve the delivery of care to his hypertensive patients.The physicians’ acceptance of and compliance with such a care system is examined, and the implications for the future are discussed.
Keywords: Computerized Medical Records; Hypertension; Long-term Management of Chronic Disease; Interactive Computerised Management of Disease; General Practice